2017
DOI: 10.1002/brb3.661
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, apathy, and depression in Alzheimer's disease and mild cognitive impairment

Abstract: IntroductionResults from studies on awareness disorders in Alzheimer's disease (AD) are controversial because the methodologies, the “objects” of awareness, and the patients' pathologic stage all vary. Our study aimed to compare scores and correlates of awareness according to the stage of the disease and the assessment method.MethodsWe compared 20 mild AD patients to 20 mild cognitive impairment (MCI) patients, using the Patient Competency Rating Scale (PCRS; patient vs. caregiver report) and the Self‐Consciou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 39 publications
3
20
2
4
Order By: Relevance
“…In contrast to research in people with dementia, we did not find a relationship between the level of awareness and the presence of depressive symptoms, although these symptoms were highly common in residents with KS (43.4%) . In people with dementia, it is hypothesized that, in particular, dysthymia can be seen as an emotional reaction of people who are aware of their progressive cognitive decline, especially in the beginning of their disease process .…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…In contrast to research in people with dementia, we did not find a relationship between the level of awareness and the presence of depressive symptoms, although these symptoms were highly common in residents with KS (43.4%) . In people with dementia, it is hypothesized that, in particular, dysthymia can be seen as an emotional reaction of people who are aware of their progressive cognitive decline, especially in the beginning of their disease process .…”
Section: Discussioncontrasting
confidence: 97%
“…These researchers were, however, cautious in interpreting their results due to the small sample size and the procedure that was followed to assess impaired awareness (clinical observation and evaluation). On the other hand and in line with our findings, several studies on people with dementia have also shown that lower levels of awareness seemed to be related to more severe apathy …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Error monitoring is a prerequisite to develop awareness of performance. There is an association between error awareness and apathy in AD, with higher levels of the latter being related to poorer awareness in people with mild AD and MCI (Jacus, 2017). It is possible that this relationship reflects the importance of emotional processing in error monitoring (Mograbi and Morris, 2014).…”
Section: Apathy and Error Monitoringmentioning
confidence: 99%